Modalities of Forgetting : A Refusal of Memory Among Post-Conflict Samburu and Pokot, Kenya - Holtzman, Jon; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2023)
Memory has, in Western societies at least, become an inseparable and unconditionally loved companion of war. In popular discourse memory appropriately honors the sacrifices and achievements of past heroes while also prescribing vigilance in the present and future: “Never Forget” so that past tragedies will “Never Again” be allowed to happen. While scholarly treatments take a more nuanced view, memory nonetheless tends to be framed as both desirable and inevitable, whether as a means to achieve justice through a true rendering of the past or to achieve closure through the honest accounting of the trauma of war. This paper problematizes these positive views of war and memory through an examination of a post-war situation among Pokot and Samburu pastoralists in northern Kenya, who emphasize the singular necessity of forgetting in order to achieve peace. The two groups fought a bitter small-scale conflict with significant loss of life and economic suffering, yet shortly after the war they had returned to a state of peaceful coexistence, intermingling and cooperating in a variety of activities. Both groups maintain that peace has been achieved by an insistence that the conflict must be forgotten, with no heroes valorized and no losses avenged. In their view to dwell on the war is to invite its return. Through this case study, the paper problematizes the positive and inevitable associations of war and memory in Western discourse and considers ‘forgetting’ both as a worthy subject of scholarly analysis and potentially a social good in the pursuit of peace.
Keywords: War; Memory; Kenya; Pastoralists; Peace